ทัศนคติต่อระบบความปลอดภัยในการทำงานของพนักงานในสถานประกอบการประเภทธุรกิจค้าปลีกตำบลแม่เหียะ อำเภอเมืองเชียงใหม่ - อภินันท์ ณ บรรพต (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this independent study was to study factors affecting the attitude of employees at Big C Supercenter Hangdong Branch towards safety system at work. The data was collected from questionnaire distributed to 300 employees and was then analyzed using descriptive statistics namely frequency, percentage and mean. It was found that most of thequestionnaire respondents were married females, 21-30 years old, with high school or vocationalschool education. They were introduced and trained about the company’s safety system beforethey started working at Big C Supercenter Hangdong Branch. For understanding factors, the respondents’ level of understanding towards the company’s security system was at the highest level, in the following order, they understood that personal protection equipment (PPE) was to be properly worn, that appropriate PPE could save them from danger during operation, that following safety rules and regulations could protect them from danger, and that PPE was compulsory for employees working at risky positions. For feeling factors, the respondents felt good about safety system at the high level in the following order, they felt that fire drill was necessary and was not a waste of time, they feltgood about the system which adhered to safety rules, and they felt bad when appointed high-risk tasks without using PPE. For behavior factors, the respondent behaviors towards safety system was at the high level, namely they properly wore PPE during operation, they were cautious at work, and they followed instructions for using equipments and machines.